Singapore : The monocle travel guide series. - Monocle, ....- (Berlin : Gestalten, 2016)
A nation-state and financial capital, this skyscraper metropolis and global business hub is also your gateway to a life less ordinary. Having become a destination in its own right, this town is anything but boring. Unlock the true Singapore. Monocle will show you how.
Keywords: reisgids